GE_GERICHTE P/24576/2016 vom 31. Januar 2018 - GE Cour de justice (2018)
VOL(DROIT PÉNAL); DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL); VIOLATION DE DOMICILE; EXPULSION(DROIT PÉNAL); EXPERTISE | CP.139.al3; CP.144; CP.20; CP.33; CP.66a; CPP.431.al3.letb